KEBIJAKAN SERTIFIKASI GURU DI SMK KARYA PEMBANGUNAN DELI TUA - Nuraini, Titi (IKAMAS: Manajemen Pendidikan Islam, 2021)
Teacher certification is one way in the world of education to improve the quality and professionalism of a teacher, so in the future all teachers must have a certificate as a teaching license or permit. Thus, efforts to establish professional teachers in Indonesia soon became a reality as expected. The teacher certification policy refers to the law on teacher lecturers number 14 of 2005 aimed at determining the feasibility of teachers in carrying out their duties as professional educators, improving learning processes and outcomes, improving teacher welfare, and improving teacher dignity, in order to realize quality national education. This goal can be achieved through an effective implementation process which can be seen from the accuracy of policies, accuracy of implementation, accuracy of targets, accuracy of the environment and accuracy of the process. This article discusses one of the educational institutions that has used teacher certification to improve the quality of teachers in the school, where this educational institution is called SMK Karya Deli Tua..